Strategi Promosi Bali Treetop Adventure Park Di Kebun Raya Eka Karya Bali, Bedugul, Kabupaten Tabanan - Azzahra, Aulia; Pujani, Luh Putu Kerti (JURNAL DESTINASI PARIWISATA; Vol 5 No 2 (2017): VOL 5, NO 2 (2017): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2018)
The tourism sector contributes a lot to the economic development in Indonesia, it can be seen from the number of new job opening, increasing the income of the state and increasing the economy of the people around the tourist destination. However, in its development, tourism has also experienced many problems, such as the increasingly tight competition among Southeast Asian countries in controlling the world tourism market target to make its region as the world's main tourist destination in the region. A poorly-organized marketing strategy can be a major problem in market target. It happened at the outbound tourist attraction of Bali Treetop Adventure Park located at Eka Karya Bali Botanical Garden, Bedugul, Tabanan Regency. Many tourists do not know the attraction of this outbound tour. This is due to lack of information for tourists about the tourist attraction, a less precise marketing strategy is suspected to be the main problem. The purpose of this research is to find out the marketing strategy of Bali Treetop Adventure Park at Eka Karya Bali Botanical Garden, Bedugul, Tabanan Regency. Types of data that is used are qualitative data and quantitative data with approaches through observation, interviews, questionnaires distribution to tourists, literature study and documentation. The data analyzed in the research is the explanation of various explanations of data obtained directly from the managers of Bali Treetop Adventure Park and tourists during this research took place. The result of this research is Bali Treetop Adventure Park has several marketing strategies that is direct promotion (sales call, exhibition, brochure), promotion of mass media (magazine, baliho, Facebook, YouTube), indirect promotion (travel agent and local guide). The target of the market has been obtained but it is not maximized, this is caused by the market strategies which is not done properly. So it is necessary to improve its performance for human resources in the tourist attraction of Bali Treetop Adventure Park is to achieve the desired number of tourists visit.   Keywords : outbond, tourist attractions, treetop